2021
DOI: 10.1108/ijem-02-2020-0113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychological factors, university environment and sustainable behaviour on teachers' intention to incorporate inclusive education in higher education

Abstract: PurposeThe current study examines the impact of various psychological factors, university environment and sustainable behaviour on teachers' intention to incorporate inclusive education in higher education.Design/methodology/approachA cross-sectional survey was conducted to collect data from 204 academicians and scholars from India. Structural equation modelling (SEM) was employed to examine data.FindingsResults revealed that teachers' attitudes, university environment and spirituality had a positive and signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…A study by Bodhi et al (2021) supports previous research that shows the importance of university environment and teachers' attitudes to inclusive education but found that also spirituality was an important factor. They suggest organisations communicate their behavioural patterns and indicate they are part of the larger society (Bodhi et al, 2021).…”
Section: Holistic Approach To Online Degree Programme Designsupporting
confidence: 79%
See 2 more Smart Citations
“…A study by Bodhi et al (2021) supports previous research that shows the importance of university environment and teachers' attitudes to inclusive education but found that also spirituality was an important factor. They suggest organisations communicate their behavioural patterns and indicate they are part of the larger society (Bodhi et al, 2021).…”
Section: Holistic Approach To Online Degree Programme Designsupporting
confidence: 79%
“…A study by Bodhi et al (2021) supports previous research that shows the importance of university environment and teachers' attitudes to inclusive education but found that also spirituality was an important factor. They suggest organisations communicate their behavioural patterns and indicate they are part of the larger society (Bodhi et al, 2021). A holistic perspective in the alignment of programme design to wider institutional practices is needed to achieve quality outcomes of ODPs as an integral part of the surrounding society.…”
Section: Holistic Approach To Online Degree Programme Designsupporting
confidence: 79%
See 1 more Smart Citation
“…Bodhi et al . (2022), in the article “Impact of psychological factors, university environment and sustainable behaviour on teachers' intention to incorporate inclusive education in higher education”, conducted a cross-sectional study on a sample of Indian academicians and scholars and explored the factors affecting teacher's intention towards inclusive higher education.…”
Section: Articles Includedmentioning
confidence: 99%
“…Furthermore, one-fifth of the population is under 21, with around 7,700,000 (77 lakh) students enrolled in higher education. Therefore, equipping students with skills to enhance their employability needs special attention to benefit from this rich and diverse human resource, which is a significant source of employees for knowledge-based work across developed nations (Bodhi et al , 2021; Shahrill et al , 2021). As stated by Gupta and Prasad (2021, online), “with 10 to 12 million youth entering the workforce every year, India should not only train and skill them for the domestic economy but for the world.”…”
Section: Introductionmentioning
confidence: 99%